Current Status of Aquarium Fish (Ornamental Fish) Enterprises During the Pandemic Period (Elazig City Sample) - Hilal Bulut; Ebru İfakat Özcan (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out in order to reveal the situation of aquarium sales enterprises in Elazig and to determine their problems. In the study, a total of 14 enterprises (aquarist) were asked questions by the survey method. It has been determined that a significant part of the existing enterprises is located in the center of Elazig (93%), all of them continue to operate as tenants and their operating periods are over 5 years. It has been noted that 86% of the personnel working in the enterprises are male and 14% are female. It was determined that the most sold fish species in the research area were 2 fish species belonging to 2 families. It has been observed that one of the important problems in aquarium businesses is fish diseases. It has been determined that 93% of the fish sales of the Covid-19 pandemic period were negatively affected and 7% were positively affected.